Genocide, culture, law: aboriginal child removals in Australia and Canada - Jago, Jacqueline (Allard Research Commons, 2009)
This thesis makes the legal argument that certain histories of aboriginal child removals in Canada and Australia, that is, the residential school experience in Canada, and the program of child institutionalization in Australia, meet the definition of 'genocide' in Article II of the Convention on the Prevention and Punishment of the Crime of Genocide. My primary focus is on that Convention's requirement that an act be committed with an "intent to destroy a group". My first concern in formulating legal argument around the Convention's intent requirement is to offer a theory of the legal subject implicit in legal liberalism. Legal liberalism privileges the individual, and individual responsibility, in order to underscore its founding premises of freedom and equality. The intentionality of the subject in this framework is a function of the individual, and not the wider cultural and historical conditions in which the subject exists. Using a historical socio-legal approach, I attempt to develop a framework of legal subjectivity and legal intent which reveals rather than suppresses the cultural forces at work in the production of an intent to genocide. Having reacquainted the subject with the universe beyond the individual, I move on with the first limb of my legal argument around intent in the Genocide Convention to address the systemic means through which child removal policy was developed and enforced. In this, I confront two difficulties: firstly, the difficulty of locating in any single person an intent to commit, and hence responsibility for, genocide; and secondly, the corresponding difficulty of finding that a system intended an action in the legal sense. I respond to both of these difficulties by arguing for a notion of legal subjectivity which comprehends organisations, and correspondingly a notion of intent which is responsive (both on an individual and an organisational level) to systematically instituted crimes such as genocide. The second limb of my argument around intent confronts the defence of benevolent intent. In this defence, enforcers of child removals rely on a genuine belief in the benevolence of the 'civilising' project they were engaged in, so that there can be no intent to destroy a group. I reveal the cultural processes at work to produce the profound disjunction between aboriginal and settler subjectivities, especially as those subjectivities crystallize around the removal of aboriginal children. I locate this disjunction in the twin imperatives of colonial culture, those of oppression and legitimation. I argue that colonial culture exacts a justification for oppression, and that aboriginal people have been "othered" (in gendered, raced, and classed terms) to provide it. Intent to destroy a group, then, will be located via an enquiry which confronts the interests of colonial culture and aligns them firstly with the oppression of aboriginal people, and secondly with the discourses which developed to render that oppression in benevolent terms. The interpretation of the Genocide Convention is thus guided by the demands of context: and in context is revealed an intent to genocide by child removal.